'Brexit' and the Scots in England: A diaspora facing uncertainty?. Issue 3 (August 2020) - Leith, Murray Stewart; Sim, Duncan
Abstract : Brexit has brought many uncertainties, including the future position of UK-based EU migrants. Our concern is with a much less studied group, albeit one of the largest socio-political sub-groups within England – the Scots. These are migrants who live in a different country but within the same state and recent constitutional decision making has not been kind to them. In 2014, English based Scots had no vote in the independence referendum and in the EU referendum they witnessed Scotland voting significantly differently to England, resulting in ongoing tensions between the UK and Scottish Governments. If Brexit leads to another independence referendum, what are the implications for Scots in England, in terms of their citizenship, identity, and residence in a very different (r)UK? We explore their status in a (r)UK outside the EU, we speculate on whether some might move back or whether, if they remain, they would experience hostility within post-Brexit England. Might the current position of the English Scots tell us something about the future relationship between England and Scotland?